2018
DOI: 10.1002/capr.12200
|View full text |Cite
|
Sign up to set email alerts
|

Facing social fears: How do improved participants experience change in mindfulness‐based stress reduction for social anxiety disorder?

Abstract: Background Clinical trials indicate that mindfulness‐based stress reduction (MBSR) may be effective for social anxiety disorder (SAD), but little is known about how young adults with SAD experience this intervention. Aim The purpose of this study was to explore how improved participants experience the process of change in MBSR for SAD. Method We used a two‐staged mixed methods design to identify participants with reliable and clinically significant improvement on primary outcome measures after an eight‐week MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…The findings reveal consistent links with existing studies-for example the report on a patient who found the verbalized feedback from the group on her blushing important [47]. Acceptance of one's own experience, whose relevance becomes clear [47,48], was not explicitly addressed, but we hypothesize that the experience of having feedback from the group resonates with our results. Interestingly, in the case of Category 1 "meeting other patients in group therapy", it is-with one exception-not the deconstructed beliefs that the leading therapist has worked out with each client, but the setting itself which gives rise to meaningful moments.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings reveal consistent links with existing studies-for example the report on a patient who found the verbalized feedback from the group on her blushing important [47]. Acceptance of one's own experience, whose relevance becomes clear [47,48], was not explicitly addressed, but we hypothesize that the experience of having feedback from the group resonates with our results. Interestingly, in the case of Category 1 "meeting other patients in group therapy", it is-with one exception-not the deconstructed beliefs that the leading therapist has worked out with each client, but the setting itself which gives rise to meaningful moments.…”
Section: Discussionsupporting
confidence: 91%
“…The findings reveal consistent links with existing studies—for example the report on a patient who found the verbalized feedback from the group on her blushing important [ 47 ]. Acceptance of one’s own experience, whose relevance becomes clear [ 47 , 48 ], was not explicitly addressed, but we hypothesize that the experience of having feedback from the group resonates with our results.…”
Section: Discussionmentioning
confidence: 58%
“…Both these summaries indicate a need for more qualitative studies of MBSR for clients with anxiety disorders. To our knowledge, only two studies have investigated MBSR for this population (A. Hjeltnes et al, 2018a , 2018b ). Hjeltnes ( 2018b ) compared how improved and less-improved participants with social anxiety disorder experienced the MBSR program, and examined how improved participants experienced their own process of change after the intervention.…”
mentioning
confidence: 99%